The Students’ Perceptions of The Implementation of ICT-Supported Project Based Learning in English Teaching - Tri Akhmad Efendi (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
The present study was aimed at investigating the students’ perceptions of the implementation of ICT-supported PBL (Project Based Learning) in English teaching at the school under the study. There were three issues covered in this study: (i) the students’ perceptions of the benefits of the implementation of ICT-supported PBL to their language skills and components, and (ii) the students’ perceptions of the benefits of the implementation of ICT- supported PBL to self-development. This study was a worth-conducting study since it was expected to help teachers see what the students’ perceptions of the implementation of ICT-supported PBL. This study was conducted on an intrinsic case study to attempt or emphasis on gaining a deep understanding of the students’ perceptions of the implementation of ICT-supported PBL at the school under the study. There were 44 students who were involved in this study. The data collected through the questionnaire and students’ reflective report. The findings were overall positive. They perceived self- development and language skills and components enhancement except the students’ perceptions of the grammar learning. To add, they felt the teaching and learning activities brought enjoyment in the classroom. There were three factors which led the students’ have positive perceptions of ICT-Supported PBL in English teaching; (a) authentic learning situations, (b) student-centered activities, and c) the involvement of ICT.